2018
DOI: 10.1002/ecs2.2174
|View full text |Cite
|
Sign up to set email alerts
|

Are seeds able to germinate before fruit color ripening? Evidence from six Neotropical bird‐dispersed plant species

Abstract: Many plants attract seed dispersers and indicate the presence of ripe, fleshy fruits with coloration changes. If seed maturation is simultaneous with visual signs for frugivorous, a portion of seeds can be removed before being ready for dispersal. In this study, we tested the delay visual signal hypothesis (DVSH), which implies high reproductive success when seed maturation precedes the visual signal of the fruit ripening, limiting the dispersal of unviable seeds. We evaluated this hypothesis with six tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…It should be kept in mind that the green fruits used in this experiment were close to ripening (they were taken from infructescences where some fruits had already turned red) and therefore that these germination results cannot be extrapolated to fruits, which are in early stages of ripening. However, fruit colour changes, normally indicative of ripening, do not affect the germination of the seeds of many species (Cruz-Tejada et al 2018). Manipulation by monkey seed dispersers does increase the rate of germination of seeds of these two Scadoxus species through the removal of fruit pulp; however, it does not affect final germination percentage (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be kept in mind that the green fruits used in this experiment were close to ripening (they were taken from infructescences where some fruits had already turned red) and therefore that these germination results cannot be extrapolated to fruits, which are in early stages of ripening. However, fruit colour changes, normally indicative of ripening, do not affect the germination of the seeds of many species (Cruz-Tejada et al 2018). Manipulation by monkey seed dispersers does increase the rate of germination of seeds of these two Scadoxus species through the removal of fruit pulp; however, it does not affect final germination percentage (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, fruit colour changes, normally indicative of ripening, do not affect the germination of the seeds of many species (Cruz‐Tejada et al . 2018). Manipulation by monkey seed dispersers does increase the rate of germination of seeds of these two Scadoxus species through the removal of fruit pulp; however, it does not affect final germination percentage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that UF seeds (control seeds from unripe fruits) had a higher probability of germination than RF seeds (control seeds from ripe fruits) by the end of the germination experiment (d 80: 60 days of shade followed by 20 days of sun exposure). Although counterintuitive (Arthur 1985), higher or similar germination success of seeds from unripe fruits, compare with mature fruits, has been reported (Foster 1977;Arditti et al 1981;Cruz-Tejada et al 2018). In the case of N. orientalis (used for control treatments), this could be an advantage to benefit from seed dispersal by animals that preferentially feed on unripe fruits, such as colobines (Davies et al 1988;Dasilva 1994;Matsuda et al 2009;Hanya and Bernard 2012;Ehlers Smith et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…However, many forest species show unevenness fruit maturation and, therefore, can produce seeds with different levels of physiological quality. In addition, there are species in which the seeds that become viable before the fruits become fully mature (Cruz-Tejada, et al, 2018). In addition, the physiological maturation process of seeds can differ between natural populations of a specie, due the genetic structure of a single plant to influence the germination potential of seeds (Yuan, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%